Utilization of Waste Vehicle Tires in Concrete and Its Effect on the Corrosion Behavior of Reinforcing Steels - Keleştemur, Oğuzhan (My University, 2010)
The mechanical and physical properties of concrete specimens obtained from replacing natural coarse aggregate with waste vehicle rubber tires at levels of 2vol%, 5vol%, 7vol%, and 10vol% were studied, and the corrosion behavior of reinforcing steels was investigated in these specimens. Corrosion rates were determined by measuring the galvanic current between steel-reinforced concrete specimens both with and without chloride addition. The change in electrode potential of reinforcing steels in these concrete specimens was measured daily for a period of 60 d in accordance with the testing method in ASTM C876. The results show that the use of waste vehicle tires in concrete instead of coarse aggregate decreases the mechanical strength of the specimens, and increases the corrosion rates of the reinforcing steels embedded in the concretes.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Vehicle tire; Concrete; Corrosion; Reinforcing steel; waste reuse